(3eONd Edi JfejI GdehGQO GdHTQjI (B:s (3OQGSI GdhGbY aj GdOhd GdYQHjI (B/s - (3HhcejT, dYdis ((3YeGf(B: s (3OGQ GdQGjI ddfTQ hGdJhRjY(B, s, 2011)
(3eGgjI JfejI GdehGQO GdHTQjI(B- (3YdGbI JfejI GdehGQO GdHTQjI HeaGgje GdJfejI(B- (3JMOjGJ hCdjGJ JfejI GdehGQO(B- (3hGbY JfejI GdehGQO GdHTQjI aj GdYGde GdYQHjs
Keywords: (3EOGQI GdCaQGOs; (3GdJfejIs; (3GdJfejI GdHTQjIs; (3GdehGQO GdHTQjIs